(untitled) (Journal of Educational Sciences, 2019)
This article covers the development and application of information systems in the aspect of the formation of the information and educational environment at the university, on the example of the al-Farabi Kazakh National University. The authors of the article analyze the existing information programs – «Univer 2.0», «Science», the accounting and personnel records system «1C: Enterprise 8.2», the time accounting system «Perco 2.0», the electronic document management system «Directum», the statistical reporting system, contact – center «VoIPTime Contact Center», on the basis of which the Corporate Information System al-Farabi KazNU. According to the authors of the article, an integral part in the formation of the information and educational space, as well as a key factor in achieving the strategic indicators of the al-Farabi KazNU is the implementation, application and development of the information and analytical system Power BI of Microsoft. Key words: information and educational environment, information systems, al-Farabi Kazakh National University, Power BI, strategic university indicators.